Internal migration in Northern Ghana: understanding the integrative challenges of migrants in Tamale Metropolis - Muhammad Mu-utasim Yahaya (Goodwood Publishing, 2021)
Purpose: Successful integration of migrants in any society has a very vital impact on the wellbeing of migrants. The study therefore uses descriptive statistics to analyse the integrative challenges of internal migrants in the Tamale metropolis of Northern Ghana. Research methodology: The study adopted the mixed-method approach and non-probability sampling techniques to select 120 internal migrants for the study. Results: The results revealed that economic factors (46.7%) accounted for most reasons cited for migrating. Language barriers (24.2%) and higher cost of living (19.2%) were the most encountered challenges and a proportion of 10.8 per cent reported not having encountered any difficulty. Limitations: The study explored all forms of internal migration in the Metropolis. However, it failed to explore the occurrence of international migration given the growing influx of international migrants in the study area. Contribution: The outcome of the study will advance knowledge on the challenges faced by migrants within the Metropolis and measures could be taken to resolve some undesired experiences. Additionally, the study will make a valuable contribution to the limited migration literature in the North.